New records of soft ticks (Acari: Argasidae) from caves in Brazil, with a morphological study of Ornithodoros fonsecai and an analysis of the taxonomic status of Antricola inexpectata - Glauber M.B. de Oliveira; Sebastián Muñoz-Leal; Santiago Nava; Maurício C. Horta; Leopoldo Bernardi; José Manuel Venzal; Marcelo B. Labruna (Ticks and Tick-Borne Diseases, 2024)
In this study, we report soft ticks from bat-inhabiting caves in different areas of Brazil. From 2010 to 2019, we collected 807 tick specimens from nine caves located in four Brazilian states among two biomes. Ticks were morphologically identified as Antricola guglielmonei (282 specimens), Ornithodoros cavernicolous (260 specimens), and Ornithodoros fonsecai (265 specimens). Whereas A. guglielmonei was collected on bat guano in hot caves, O. cavernicolous and O. fonsecai were collected in cracks and crevices on the walls of cold caves, sometimes in the same chamber. Morphological identifications were corroborated by molecular and phylogenetic analyses inferred from tick mitochondrial 16S rRNA gene partial sequences. The sequences of A. guglielmonei, O. cavernicolous and O. fonsecai collected in this study clustered with conspecific GenBank sequences from different localities of Brazil. Remarkably, a clade containing 12 sequences of O. fonsecai was clearly bifurcated, denoting a degree of genetic divergence (up to 5 %) of specimens from Cerrado/Atlantic Forest biomes with the specimens from the Caatinga biome. To further evaluate this divergence, we performed morphometric analysis of the larval stage of different O. fonsencai populations by principal component analysis, which indicated that the larvae from Caatinga populations were generally smaller than the larvae from other biomes. Some of the present A. guglielmonei specimens were collected from the type locality of Antricola inexpectata. Comparisons of these specimens with the type specimens of A. inexpectata and A. guglielmonei indicated that they could not be separated by their external morphology. Hence, we are relegating A. inexpectata to a synonym of A. guglielmonei. This proposal is corroborated by our phylogenetic analysis.